Road accident-related mortality in the tunja-san gil area, colombia, 2001 (2003)
Objectives: To identify the characteristics of mortality related to motor vehicle accidents in the Tunja-San Gil area (Colombia) in the year 2001. Methods:  A descriptive study was performed on the deaths from road accidents. Autopsy reports, body removal reports, death certificates and blood concentration reports, available at the National Institute for Forensic Sciences and at the local hospitals, were reviewed. Results: Forty five fatalities were analyzed. The mean age of the victims was 34,7 years; males were more affected than females, with a 3:1 ratio. 37% were pedestrians, 26% motorcyclists, 20% drivers, 8,6% cyclists and 8,6% passengers. 65,1% of the road accidents occurred during weekends. The most common road accidents were either collisions or by running over. The places with the highest rates of death from motor vehicle related accidents were the urban areas of Tunja and San Gil and the Vado Real-Oiba road. The mean Injury Severity Score was 42,8. 53% of the deaths at the scene received no medical care; 73% of the victims died within two hours after the motor-vehicle accident. 17,8% of deaths were definitely preventable and 46,7% were possibly preventable, for a combined preventable death rate of 64,5 %. Conclusions: It is necessary to develop and implement a road-accident related-trauma care system.